Coping with dark leadership: Examination of the impact of psychological capital on the relationship between dark leaders and employees' basic need satisfaction in the workplace - Alina Elbers; Stephan Kolominski; Pablo Salvador Blesa Aledo (Administrative Sciences, 2023)
In leadership research, the Dark Triad of personality has become a topic of great interest. This construct includes the personality traits of narcissism, Machiavellianism, and subclinical psychopathy and is associated with several negative outcomes for organizations and followers' satisfaction. In contrast, the construct of psychological capital, which includes hope, resilience, self-efficacy, and optimism, is positively related to extra-role organizational citizenship behaviors and employee performance. Therefore, the question arises whether people can benefit from psychological capital when confronted with a manager that exhibits dark personality traits. Subsequently, the purpose of this study is to examine the potential impact of psychological capital on the relationship between the Dark Triad traits of managers and the work-related basic need satisfaction of employees. Thus, a dataset of 469 employees was analyzed. Regression analyses demonstrated that the Dark Triad of personality and psychological capital both work as predictors of work-related basic need satisfaction. When controlling for mediating effects, psychological capital appeared as a partial mediator of the relationship between the managers' dark traits and the employees' basic need satisfaction in the workplace. The theoretical and practical implications of the results, as well as suggestions for future research, are discussed.
Keywords: 350; basic need satisfaction; Dark Triad of personality; leadership; psychological capital; Self-Determination Theory